Measurement of mean raindrop shape from polarimetric radar observations - Gorgucci, Eugenio, author; Chandrasekar, V., author; Scarchilli, Gianfranco, author; Bringi, V. N., author; American Meteorological Society, publisher (Colorado State University. Libraries, 2000)
Interpretation of polarimetric radar measurements in rainfall such as differential reflectivity and specific differential phase shifts depends on the mean raindrop shape-size relationship. Currently, semiempirical relations between the oblateness and the diameter of the drop are being used. This paper presents an algorithm to obtain the mean shape of the rain drops from polarimetric radar measurements, namely, the reflectivity factor, the differential reflectivity and the specific differential phase shift. The accuracy of the estimate mean drop shape depends on the measurement accuracies of polarimetric radar observations. Based on asymptotic error analysis and simulations it is shown that the mean raindrop shape can be estimated to an accuracy of 10%. The raindrop shape estimator algorithm developed in this paper is applied to polarimetric radar data collected by the CSU-CHILL radar during the 28 July 1997 Fort Collins. Colorado, flood.